Paediatric hereditary angioedema: a survey of UK service provision and patient experience. (7th November 2014) - Read, N; Lim, E; Tarzi, M D; Hildick-Smith, P; Burns, S; Fidler, K J
Summary: Hereditary angioedema (HAE) is a rare disease characterized by episodes of potentially life-threatening angioedema. For affected children in the United Kingdom, there are relatively few data regarding disease prevalence, service organization and the humanistic burden of the disease. To improve knowledge in these areas, we surveyed major providers of care for children with HAE. A questionnaire was sent to major paediatric centres to determine patient numbers, symptoms, diagnostic difficulties, management and available services. In addition, all patients at a single centre were given a questionnaire to determine the experiences of children and their families. Sixteen of 28 centres responded, caring for a total of 111 UK children. Seven children had experienced life-threatening crises. One-third of patients were on long-term prophylactic medication, including C1 inhibitor prophylaxis in four children. Eight centres reported patients who were initially misdiagnosed. Broad differences in management were noted, particularly regarding indications for long-term prophylaxis and treatment monitoring. We also noted substantial variation in the organization of services between centres, including the number of consultants contributing to patient care, the availability of specialist nurses, the availability of home therapy training and the provision of patient information. Ten of 12 patient/carer questionnaires were returned, identifying three common themes: the need to access specialist knowledge, the importance of home therapy and concerns around the direct effect of angioedema on their life. To our knowledge, this study represents the first dedicated survey of paediatric HAE services in the United Kingdom and provides useful information to inform the optimization of services.